Iatrogenic Vascular Injuries of the Abdomen and Pelvis: The Experience at a Hellenic University Hospital. (October 2019) - Filis, Konstantinos; Sigala, Fragiska; Stamatina, Triantafyllou; Georgia, Doulami; Zografos, Georgios; Galyfos, George
Background: The aim of this study is to present the experience of a Vascular Division at a Hellenic University hospital concerning the management of iatrogenic vascular injuries (IVIs) of the abdomen or pelvis. Patients and Methods: This is a retrospective study evaluating all IVIs reported during a 10-year period in our institution. Only injuries warranting a vascular surgeon consultation were included in the study. Non-iatrogenic injuries were not included. Mortality and major complications within 30 days were evaluated. Results: Overall, 70 cases were recorded, with 41% being venous and 59% being arterial injuries. Iliac arteries (51%) were the most common location and rupture/lacerations (73%) were the most common type of injury. General surgery (61.5%) and cardiology (30%) procedures were the most frequently involved procedures. A 30-day mortality was 5.7%, with 30% of cases treated conservatively. Synthetic bypass grafting (odds ratio [OR] = 65.0; 95% confidence interval [CI], 4.022-1050.358; P = .003) and male gender (OR = 83.77; 95% CI, 4.040-1736.738; P = .004) were associated with death. Conclusions: Iatrogenic vascular injuries of the abdomen or pelvis are usually associated with general surgery and endovascular procedures. When vascular consultation is requested early, mortality could remain low. However, a selected number of stable patients with retroperitoneal or pelvic hematomas could be treated conservatively, yielding satisfying results.